ENT 530 Social Media Portfolio: Reyna Hijab / Radin Nur Adriana Radin Abdul Razak - Radin Abdul Razak, Radin Nur Adriana (2021)
This report is to present a social media portfolio regarding the business named 'Reyna Hijab.' It specializes in selling women's hijab for hijabis or non-hijabis in Malaysia through the only social media platform, such as Facebook. It offering the best quality of fabrics of headscarves to the consumers in Malaysia and ensure the customer will get the best experiences with every purchase of the product of Reyna Hijab. Reyna Hijab is headquartered in Johor specify in Batu Pahat and owned by a woman aged 22 years old named Radin Nur Adriana Binti Radin Abdul Razak, a student of UiTM Puncak Alam that has little experience in a startup the online business. Not enough than that, she is also the only one taking hands-on all the management roles in this business where including the marketing or the production itself. Reyna Hijab is very concerned about product quality and puts customer satisfaction first, among others. To let the customer have various choices that can be chosen, it provided a variety of headscarves such as Shawl and Square Scarves that are common hijab for the hijabi worldwide. It also provided different types of shawls and square scarves materials to the consumers, including satin silk, chiffon and cotton. The hijab business has seen an explosion of growth day by day, probably because the hijab is a high-demand product worldwide. The product also required all Muslim women out here to wear to according to the Islam regulations. Even the hijab business is already operated by many, it does not stop the Reyna Hijab from continuing to operate and grow and learn to survive in this competitive market. Reyna Hijab's business emphasizes the quality of the product itself at the prices that everyone can afford. First, it has to start with a few requirements to fulfill the Principle of Entrepreneurship (ENT 530) subject requirement, a teaser at the introduction stage and followed by the post that has its own special transferring information which includes soft sell and a hard sell in each process advertise the product.